2015
DOI: 10.1002/app.43053
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanical and interfacial properties of core–shell structured bamboo–plastic composites

Abstract: Core-shell structured bamboo-plastic composites (BPCs) were directly prepared with a single-screw/single-screw coextruder system. The effects of different shell layers, such as high-density polyethylene (HDPE), bamboo pulp fiber (BPF)/HDPE, and white mud (WM)/HDPE, were studied in the context of the mechanical properties and the characteristics of the interfacial transition zone (ITZ) of BPC. The mechanical properties of the core-shell structured BPC were characterized by flexure, short-beam shear, and impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The dynamic mechanics performance of a material can reflect its interfacial properties [17,29] and provides a convenient visual analysis method for characterizing interfacial properties, which also can be used for reference. The interface between the fibers and matrix can be quantified using a hybrid model of the loss factor according to previous research [33,38].…”
Section: The Interfacial Properties Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic mechanics performance of a material can reflect its interfacial properties [17,29] and provides a convenient visual analysis method for characterizing interfacial properties, which also can be used for reference. The interface between the fibers and matrix can be quantified using a hybrid model of the loss factor according to previous research [33,38].…”
Section: The Interfacial Properties Of Compositesmentioning
confidence: 99%
“…The surface free energy not only evaluates the macroscopic property of the material, but it can also associate with the microscopic phenomena of the material [16]. Additionally, the structure of the composites, the compatibility of each component in the composites, and the relationships between mobility of the polymer chains and performance of the composites can be reflected by dynamic mechanical analysis [17]. Hong et al [18] noted that dynamic mechanical flexural properties exhibit sensitivity to the interfacial adhesion between the lignocellulose and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hao et al (2019) showed that incorporation of nano-scale size silica particles filled shells improved the flexural properties, impact strength, and creep behavior of coextruded wood fiber/plastic composites (WF/HDPE). The authors previously demonstrated improved strength and toughness of bamboo fiber reinforced plastic composites after the addition of white mud in wood-plastic composites and coextruded wood-plastic composites (Ren et al 2014;Xian et al 2016). The presence of white mud in the shell layer may also improve the thermal stability of core shell structured wood-plastic composites.…”
Section: Introductionmentioning
confidence: 99%
“…6 Also, with the rapid development of the market and customer demands for enhanced properties of the final product, traditional WPCs have failed to deliver on specific quality requirements, such as enhanced mechanical properties and lower water absorption (WA). 7,8 The plastic materials produced from petroleum are relatively easy to recycle. Thus governments in many countries have focused their efforts on recycling these waste plastics to reduce the volume of material going into landfills.…”
Section: Introductionmentioning
confidence: 99%